La végétation des Petites Antilles : principaux traits floristiques et effets plausibles du changement climatique - Philippe Joseph (VertigO)
According to all spatial scales, the uneven topography of the Lesser Antilles leads to a great lot of biotops. So, from species to landscapes, through phytocenoses and ecosystems, numerous types of floristic organisation occur. Despite an important anthropization, this archipelago belongs to one of the Hotspots of the planetary biodiversity: the Caribbean. In the Long-Term, climatic change will have consequences on the spatial distribution and on the function of species and vegetal associations.